Management of post-operative sore throat in patients undergoing endotracheal intubation: literature review - El Sharkawy, Ahmed M.; Rawas, Mustafa M.; Altoies, Amany M.; Al Arbash, Mohammed A.; Alzahrani, Abdulaziz A.; Alnahari, Anas M.; Alomari, Khaled S.; Hammad, Ziyad H.; Ebrahim, Basel M.; Alqahtani, Mansour M.; Alshahrani, Ali S. (International Journal Of Community Medicine And Public Health, 2021)
Postoperative sore throat (POST) is a common complaint that is classified as the 8th most undesirable events after general anesthesia. Endotracheal intubation has been estimated to be the commonest factor causing POST. We aim to review the risk factors and preventive measures to reduce the incidence and severity of POST following endotracheal intubation. Although sore throat can be induced by many perioperative factors, endotracheal intubation remains the commonest cause that can induce endothelial injury and a subsequent sore throat. Many risk factors for this association has been reported. The most common risk factors include ages less than 60 years of age, female sex, cough, and asthma, underlying chest diseases, type and timing of the operation, type, and size of the used endotracheal tube. Moreover, the experience of the personnel intubating the patients may have been another risk factor. Medical prevention of POST can be achieved by several agents as steroids, non-steroidal anti-inflammatory drugs (NSAIDS), N-methyl-D-aspartate (NMDA) receptor antagonists, careful monitoring of the tracheal cuff pressure, and licorice application. On the other hand, using lidocaine has been contraindicated according to previous meta-analysis results. Additionally, we recommend that future studies with bigger sample sizes are should be conducted for further validation of the new modalities.